Recent Progress in the Study of Peroxiredoxin in the Harmful Algal Bloom Species Chattonella marina - Yohei Shimasaki; Koki Mukai; Yuki Takai; Xuchun Qiu; Yuji Oshima (MDPI AG, 2021)
Peroxiredoxin (Prx) is a relatively recently discovered antioxidant enzyme family that scavenges peroxides and is known to be present in organisms from biological taxa ranging from bacteria to multicellular eukaryotes, including photosynthetic organisms. Although there have been many studies of the Prx family in higher plants, green algae, and cyanobacteria, few studies have concerned raphidophytes and dinoflagellates, which are among the eukaryotic algae that cause harmful algal blooms (HABs). In our proteomic study using 2-D electrophoresis, we found a highly expressed 2-Cys peroxiredoxin (2-CysPrx) in the raphidophyte Chattonella marina var. antiqua, a species that induces mass mortality of aquacultured fish. The abundance of the C. marina 2-CysPrx enzyme was highest in the exponential growth phase, during which photosynthetic activity was high, and it then decreased by about a factor of two during the late stationary growth phase. This pattern suggested that 2-CysPrx is a key enzyme involved in the maintenance of high photosynthesis activity. In addition, the fact that the depression of photosynthesis by excessively high irradiance was more severe in the 2-CysPrx low-expression strain (wild type) than in the normal-expression strain (wild type) of C. marina suggested that 2-CysPrx played a critical role in protecting the cell from oxidative stress caused by exposure to excessively high irradiance. In the field of HAB research, estimates of growth potential have been desired to predict the population dynamics of HABs for mitigating damage to fisheries. Therefore, omics approaches have recently begun to be applied to elucidate the physiology of the growth of HAB species. In this review, we describe the progress we have made using a molecular physiological approach to identify the roles of 2-CysPrx and other antioxidant enzymes in mitigating environmental stress associated with strong light and high temperatures and resultant oxidative stress. We also describe results of a survey of expressed Prx genes and their growth-phase-dependent behavior in C. marina using RNA-seq analysis. Finally, we speculate about the function of these genes and the ecological significance of 2-CysPrx, such as its involvement in circadian rhythms and the toxicity of C. marina to fish.